2022
DOI: 10.1101/2022.05.26.493598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of an expanded antibody toolset that captures alpha-synuclein pathological diversity in Lewy body diseases

Abstract: The abnormal aggregation and accumulation of alpha-synuclein (aSyn) in the brain is a defining hallmark of synucleinopathies. An increasing number of studies show that aSyn in pathological aggregates exists as a complex mixture of various post-translationally modified forms and conformations. The distribution of these different species changes during disease progression and varies among the different synucleinopathies. Current approaches for detecting aSyn in human tissues and disease models rely on a limited … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 122 publications
1
9
0
Order By: Relevance
“…Next, we proceed to the second step—antibody immobilization. Here, we chose a sequence-specific antibody targeting the flexible C-terminal domain of the protein: SYN-211, as the capturing agent that binds to full-length aSyn irrespective of its conformation, thereby enabling unbiased structural analysis of the protein ( 55 ). The antibody solution is injected at ~30 min, and we note an increase in the sensorgram, indicating the binding of the antibody on the thiolated sensing element ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we proceed to the second step—antibody immobilization. Here, we chose a sequence-specific antibody targeting the flexible C-terminal domain of the protein: SYN-211, as the capturing agent that binds to full-length aSyn irrespective of its conformation, thereby enabling unbiased structural analysis of the protein ( 55 ). The antibody solution is injected at ~30 min, and we note an increase in the sensorgram, indicating the binding of the antibody on the thiolated sensing element ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the use of antibodies against different regions and post-translational modifications of aSyn enables revealing the pathological diversity across synucleinopathies (Altay et al, 2022). Therefore, we sought to use an expanded antibody tool box to characterize the aSyn astrocytic pathology.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, antibodies to multiple epitopes, including those targeting the N terminus, have been shown to provide more detailed information on other oligomer subtypes and locations in the brain. 72,73 (iii) Detailed characterisation of the disease-specific oligomer population: this will require super-resolution methods or electron microscopy to visualise nanoscale structures. To use super-resolution methods, further signal-to-noise ratio improvement is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, antibodies to multiple epitopes, including those targeting the N terminus, have been shown to provide more detailed information on other oligomer subtypes and locations in the brain. 72,73…”
Section: Discussionmentioning
confidence: 99%